INTERVENSI LATIHAN RANGE OF MOTION (ROM) AKTIF PADA EKSTREMITAS ATAS TERHADAP PERUBAHAN EMOSIONAL PADA PASIEN PASCA STROKE DI POLI SARAF RUMAH SAKIT ISLAM SURABAYA - Eppy Setiyowati; H Zuhrotul Ilmiyah (Universitas Nahdlatul Ulama Surabaya, 2016)
After stroke, patients experience emotional changes resulted from the pain caused by stroke attack; it is normal reactions to the challenge, fear, and frustration in facing their disabilities. This study was purposed to find out the effectiveness of active range of motion exercises on upper extremities for the emotional changes after stroke. The study using quasi-experimental design involved the population of all patients found in the Neurology Polyclinic of RSI Surabaya. The samples of 20 respondents were collected using consecutive sampling technique. The independent variable was the active range of motion exercises, whereas the dependent variable was the emotional changes. The collected were analyzed using ttest with the level of significance α = 0.05. The result of study showed a significant difference on the treatment group before and after the intervention of active range of motion exercises was done, whereas no significant difference was found in the control group. Moreover, the result of t-test in the treatment group showed that P = 0.003 < α = 0.05 so that H0 was rejected. In contrast, the result of t-test in the control group showed that P = 0.530 > α = 0.05 so that H0 was accepted. It illustrated that active range of motion exercises was effective for the emotional changes in the control group. In conclusion, active range of motion exercises was effective for the emotional changes happening in post-stroke patients in facing their disabilities. Key words: post-stroke, emotional changes, range of motion (ROM)